The Effect of Augmented Reality-Based First Aid Health Education On Youth Red Cross at Titian Teras State Senior High School in Jambi City - Andi Subandi; Dwi Noerjoedianto; Iis Hartini; Tiara Kamila Dyanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Health education is a crucial aspect of guiding learners about health in a broad range, encompassing physical, mental, and social well-being. Schools, being environments where students are exposed to various hazards, are particularly vulnerable to accidents. First aid education is essential in preventing injuries and ensuring that students are equipped with the necessary skills to respond effectively in emergency situations. This study aims to evaluate the effect of Augmented Reality (AR) based First Aid health education on the knowledge of Youth Red Cross (PMR) members at Titian Teras State Senior High School, Jambi City. This study employed a quasi-experimental design with one pretest-posttest group without a control group. A total of 50 PMR members were involved, divided into an intervention group (n=25) and a control group (n=25). The intervention group received AR-based First Aid health education, while the control group received conventional methods. Data collection was conducted using a knowledge assessment tool, and pre- and post-test analyses were performed to evaluate the effectiveness of the intervention. The results showed a significant increase in the intervention group's knowledge. After the intervention, 80% of respondents in the intervention group achieved the